Modified aramid fiber as well as preparation method and application thereof

Through oxygen plasma treatment and carbon nanotube grafting technology, the problems of acid-base corrosion and complex processes in the aramid fiber modification process in the existing technology are solved, and the interface performance and mechanical properties of aramid fiber composite materials are improved, so as to achieve Industrialized continuous preparation.

CN119265926AActive Publication Date: 2025-01-07BEIJING GRAPHENE INST +1

Patent Information

Application Number
CN202411596701.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-01-07
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

The prior art uses acid or alkali in the process of modifying aramid fiber to cause damage to the surface structure of the fiber, and the process is complicated and the industrial continuous preparation cannot be achieved, resulting in poor interfacial adhesion performance of the aramid fiber composite material.

Method used

The aramid fiber is treated with oxygen plasma to form a carboxy group, and then connected to carbon nanotubes with a length of 1 to 5 μm. The carbon nanotubes are grafted with polymers containing amino groups, and the fiber surface roughness and interface bonding are improved through covalent bonding. force.

Benefits of technology

The interface performance and mechanical properties of aramid fiber composite materials are significantly improved, the defects at the interface of fiber composite materials are reduced, and a simple and efficient continuous production method is realized.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119265926A_ABST
    Figure CN119265926A_ABST
Patent Text Reader

Abstract

The invention discloses a modified aramid fiber as well as a preparation method and application thereof. The modified aramid fiber comprises an aramid fiber and a carbon nanotube, the aramid fiber and the carbon nanotube are connected through an amido bond, the length of the carbon nanotube is 1-5 [mu] m, and the surface of the carbon nanotube is grafted with an amino-containing polymer. According to the modified aramid fiber disclosed by the invention, the surface roughness of the aramid fiber is improved due to the fact that the carbon nanotubes with the length of 1-5 microns are grafted on the surface, so that the aramid fiber and the epoxy resin generate a mechanical locking effect. Furthermore, the amino groups on the surface of the modified aramid fiber are covalently bonded with the epoxy resin, so that the bonding force between the fiber and the resin is further improved. In addition, the modulus of the introduced interface layer is between the modulus of the resin and the modulus of the aramid fiber, so that the defects at the interface of the fiber composite material under working conditions can be reduced. Meanwhile, the modified aramid fiber can be continuously produced, the treatment process is simple, efficient and green, and industrial amplification is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aramid fibers, and in particular relates to a modified aramid fiber and a preparation method and application thereof. Background Art

[0002] Aramid fiber, also known as aromatic polyamide fiber, is about 20% lighter than carbon fiber and has a density of about 60% of the same glass fiber. It has the characteristics of high modulus, high strength, high temperature resistance, low hysteresis loss, fatigue resistance, and low linear expansion coefficient. It can be used as the main reinforcement material for resin and rubber. However, due to the high crystallinity of the surface layer of aramid fiber, the surface is smooth and chemically inert, and the interfacial adhesion with the resin or rubber matrix is ​​poor, resulting in poor mechanical effectiveness of aramid fiber. Therefore, it is of great significance and application value to modify the surface of aramid fiber to enhance the interfacial adhesion performance of aramid fiber composites.

[0003] In recent years, a variety of fiber surface modification methods have been developed, which are mainly divided into physical modification and chemical modification. The most common physical modification is coating treatment, that is, coating a resin with functional groups on the fiber surface to improve the mechanical properties of fiber composites by inhibiting the expansion of cracks. Chemical modification refers to the replacement or hydrolysis of amide bonds on the fiber surface under certain conditions to generate functional groups such as hydroxyl and carboxyl on its surface. Although the chemical modification process is complicated, the modification effect is often better than physical coating modification. Studies have shown that small molecules such as dopamine, latex, and coupling agents can be uniformly bonded to the fiber surface through strong physical adhesion or chemical reaction, and increase the roughness and surface polarity of the fiber through grafting or self-polymerization reaction, thereby enhancing the bonding strength between the fiber and the matrix material.

[0004] The existing technology can improve the surface polarity and surface roughness of fibers to a certain extent by using small molecule modifiers, which greatly improves the performance of aramid fiber composites. However, the use of acid or alkali in the modification process is inevitable, and the corrosion of acid or alkali usually destroys the surface structure of the fiber, resulting in a decrease in the strength of the fiber itself. In addition, the process takes a long time and cannot be achieved for industrial continuous preparation. Therefore, it is of great significance to find a suitable process, combining surface physical coating and chemical grafting reaction to prepare modified aramid fibers with excellent performance. Summary of the invention

[0005] In order to solve the above problems, the present invention provides an aramid fiber and a preparation method and application thereof.

[0006] The invention provides a modified aramid fiber, comprising aramid fiber and carbon nanotubes, wherein the aramid fiber and the carbon nanotubes are connected via amide bonds, the carbon nanotubes are 1 to 5 μm long, and polymers containing amino groups are grafted onto the surfaces of the carbon nanotubes.

[0007] According to one embodiment of the present invention, based on the total molar weight of atoms on the surface of the modified aramid fiber being 100%, the amino content on the surface of the modified aramid fiber is 8-40%.

[0008] According to another embodiment of the present invention, based on the total mass of the modified aramid fiber being 100%, the mass content of the carbon nanotubes in the modified aramid fiber is 0.2-5%.

[0009] The present invention also provides a method for preparing the modified aramid fiber, comprising: S1, treating the aramid fiber with oxygen plasma to generate carboxyl groups on the surface of the aramid fiber; S2, using carbon nanotubes with a length of 1 to 5 μm and with carboxyl groups on the surface of the carbon nanotubes, and then grafting a polymer containing amino groups onto the surface of the carbon nanotubes to form amino carbon nanotubes; S3, grafting the amino carbon nanotubes onto the surface of the aramid fiber.

[0010] According to one embodiment of the present invention, in the step S1, the aramid fiber is plasma treated in an oxygen atmosphere at a power range of 150 to 700 W.

[0011] According to another embodiment of the present invention, in the step S2, based on the total molar amount of carbon nanotube surface atoms with carboxyl groups as 100%, the carboxyl content on the surface of the carbon nanotubes is 3-30%.

[0012] According to another embodiment of the present invention, in the step S2, the polymer containing amino functional groups is one or more of polyetheramine, polyallylamine, polyacrylamide, polyethyleneimine and polyamidoamine, and the weight average molecular weight of the polymer is more than 2000 and less than 20000.

[0013] According to another embodiment of the present invention, in the step S3, the aramid fiber treated with oxygen plasma is reacted with an amino carbon nanotube aqueous dispersion at a temperature of 60°C to 300°C for 2min to 40min, so that the amino group reacts with the carboxyl group on the surface of the aramid fiber to form a covalent bond.

[0014] The present invention further provides an aramid fiber resin composite material, comprising the modified aramid fiber.

[0015] According to one embodiment of the present invention, the composite material further comprises epoxy resin, and amino groups on the surface of the modified aramid fiber are covalently bonded to the epoxy resin.

[0016] The modified aramid fiber of the present invention has a surface grafted carbon nanotube with a length of 1 to 5 μm, which improves the surface roughness of the aramid fiber, so that it can be combined with epoxy resin to form a mechanical locking effect with the epoxy resin, and the amino group on the surface of the aramid fiber can produce covalent bonding with the epoxy resin, thereby improving the bonding force between the fiber and the resin. In addition, the modulus of the introduced interface layer (carbon nanotube layer) is between that of the resin and the aramid fiber, which can reduce the defects at the interface of the fiber composite material under working conditions. The use of the modified aramid fiber can significantly improve the interface performance and comprehensive mechanical properties of the aramid fiber composite material. The continuous production method is simple, efficient, green, and conducive to industrial scale-up. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 It is a schematic flow chart of a method for preparing modified aramid fiber according to one embodiment of the present invention.

[0018] Figure 2 It is a schematic diagram of a preparation process of modified aramid fiber according to another embodiment of the present invention.

[0019] Figure 3 This is an electron microscope photograph of the untreated aramid fiber in Example 1.

[0020] Figure 4 This is an electron microscope photograph of the aramid fiber after oxygen plasma treatment in Example 1.

[0021] Figure 5 This is an electron microscope photograph of the amino-grafted carbon nanotube aramid fiber in Example 1.

[0022] Figure 6 This is an electron microscope photograph of aramid fibers after being pulled out from a composite material formed by untreated aramid fibers.

[0023] Figure 7 This is an electron microscope photograph of aramid fibers after being pulled out from a composite material formed by aramid fibers treated with oxygen plasma.

[0024] Figure 8 This is an electron microscope photograph of the aramid fiber after being pulled out from the composite material formed by the modified aramid fiber prepared in Example 1. DETAILED DESCRIPTION

[0025] The present invention is described in detail below in conjunction with specific implementation modes.

[0026] The modified aramid fiber of the present invention comprises aramid fiber and carbon nanotubes, wherein the aramid fiber and the carbon nanotubes are connected through an amide bond (-CO-NH-), the carbon nanotubes (CNT) are 1 to 5 μm in length, and a polymer containing amino groups is grafted on the surface of the carbon nanotubes. The surface roughness of the aramid fiber is improved due to the carbon nanotubes with a length of 1 to 5 μm grafted on the surface, so that a mechanical locking effect is generated between the aramid fiber and the epoxy resin, thereby improving the bonding force between the fiber and the resin. Furthermore, the polymer containing amino groups is grafted on the surface of the carbon nanotubes, that is, the amino groups on the surface of the modified aramid fiber can be covalently bonded with the epoxy resin, further enhancing the bonding strength between the aramid fiber and the resin. Thus, the interface properties and mechanical properties of the aramid fiber composite material are further improved. Moreover, the introduced interface layer modulus is between the resin and the aramid fiber, which can reduce the defects at the interface of the fiber composite material under working conditions. The use of the modified aramid fiber can significantly improve the interface properties and comprehensive mechanical properties of the aramid fiber composite material.

[0027] In an optional embodiment, the total molar amount of atoms on the surface of the modified aramid fiber is 100%, and the amino content on the surface of the modified aramid fiber is 8-40%. The amino groups in the modified aramid fiber can covalently bond with the epoxy resin to enhance the interfacial bonding force. Therefore, those skilled in the art can reasonably select any value of the mass content of the amino groups in the modified aramid fiber within the above range according to actual needs, such as but not limited to 8%, 10%, 15%, 20%, 25%, 30%, 35% and 40%, etc.

[0028] In an optional embodiment, the mass content of carbon nanotubes on the surface of the modified aramid fiber is 0.2-5%, based on the total mass of the modified aramid fiber being 100%. The content of carbon nanotubes in the modified aramid fiber determines the surface roughness of the fiber and the amount of polymers containing amino groups that can be grafted. Those skilled in the art can select any value of the content of carbon nanotubes within the above range according to actual needs, such as but not limited to 0.2%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% and 5%, etc.

[0029] Combine the following Figure 1 The preparation method of modified aramid fiber according to one embodiment of the present invention is explained. The preparation method of modified aramid fiber according to the present invention comprises: S1, treating aramid fiber with oxygen plasma to generate carboxyl groups on the surface of aramid fiber; S2, providing carbon nanotubes, wherein the carbon nanotubes are 1 to 5 μm in length and have carboxyl groups on the surface of the carbon nanotubes, and then grafting a polymer containing amino groups onto the surface of the carbon nanotubes to form amino carbon nanotubes; S3, grafting the amino carbon nanotubes onto the surface of the aramid fiber.

[0030] In step S1, the aramid fiber surface is treated to carry a large number of carboxyl groups. The specific parameters of the oxygen plasma treatment can be plasma treatment of the aramid fiber in an oxygen atmosphere at a power range of 150 to 700 W. In the present invention, oxygen plasma is used to treat the aramid fiber, and the surface roughness and carboxyl content of the fiber are controlled by controlling the atmosphere, power and movement rate. At the same time, carboxyl groups can be generated on the surface of the aramid fiber, effectively increasing the number of subsequent amino-containing carbon nanotubes grafted on the surface of the aramid fiber. In addition, the oxygen plasma treatment of aramid fiber can be carried out continuously, with a stable effect and little damage to the fiber.

[0031] In step S2, a polymer containing amino groups is grafted onto the surface of the carbon nanotubes. The polymer containing amino groups reacts with carbon nanotubes with carboxyl groups, that is, the amino groups in the polymer react with the carboxyl groups on the surface of the carbon nanotubes to form amide bonds, and the polymer containing amino groups is grafted onto the surface of the carbon nanotubes to obtain amino-modified carbon nanotubes.

[0032] In an optional embodiment, the total molar amount of carbon nanotube surface atoms with carboxyl groups is 100%, and the carboxyl content of the carbon nanotube in this step is 3-30%. As mentioned above, the polymer containing amino groups reacts with the carboxyl groups on the surface of the carbon nanotubes to form amide bonds, and the polymer containing amino groups is grafted to the surface of the carbon nanotubes. Therefore, the carboxyl content on the surface of the carbon nanotubes can determine the amount of polymers that can be grafted to the surface of the carbon nanotubes. Therefore, those skilled in the art can select an appropriate carboxyl content in the carbon nanotubes according to actual needs, such as but not limited to 3%, 10%, 15%, 20%, 25% and 30%, etc.

[0033] In step S2, carbon nanotubes of a specific length and a specific carboxyl content can be formed by any appropriate means. For example, but not limited to, carbon nanotubes that meet the requirements can be purchased from the market, or the carbon nanotubes can be chopped and surface carboxylated to achieve the desired length and carboxyl content. In the present invention, in order to ensure the mechanical strength of the surface-modified aramid fiber, the length of the carbon nanotubes needs to be controlled at 1 to 5 μm. If the carbon nanotubes are too short (less than 1 μm), it is difficult to wrap around the fiber surface. If the carbon nanotubes are too long (greater than 5 μm), they will entangle with each other, resulting in poor dispersion, and it is difficult for the carbon nanotubes to be evenly grafted on the surface of the aramid fiber.

[0034] The polymer containing amino functional groups is one or more of polyetheramine, polyallylamine, polyacrylamide, polyethyleneimine and polyamidoamine. Preferably, the weight average molecular weight of the polymer is between 2000 and 20000. If the weight average molecular weight of the polymer is within the above range, the content of the amino group can be guaranteed to be within a certain range, and at the same time, the length of the polymer can be guaranteed not to be too large to form a steric hindrance that affects its grafting to the surface of the carbon nanotube. Those skilled in the art can select a polymer of any molecular weight in the above weight average molecular weight range according to actual needs, for example, but not limited to, the weight average molecular weight can be 2000, 5000, 10000, 15000, 20000, etc. The specific grafting reaction process can be: adding carbon nanotubes and polymers to methanol, treating the mixed solution with an ultrasonic system for 10min to 2h, so that the two are evenly dispersed in methanol, and then reacting the dispersion system at 50 to 100°C for 5 to 24h, so that the polymer is grafted on the surface of CNT to obtain amino carbon nanotubes.

[0035] There is no order requirement for steps S1 and S2. The two steps can be performed simultaneously or one after the other (i.e., any one of S1 and S2 can be performed first).

[0036] In step S3, the aramid fiber with carboxyl groups on the surface is reacted with the polymer containing amino groups grafted on the surface, that is, the carboxyl groups and the amino groups form amide bonds to connect the carbon nanotubes to the surface of the aramid fiber. The specific process can be: adding the prepared amino carbon nanotubes to water to form a carbon nanotube aqueous dispersion, and then the treated aramid fiber is passed through the amino carbon nanotube aqueous dispersion, and reacted at a temperature of 60°C to 300°C for 2min to 40min, so that the amino groups react with the carboxyl groups on the surface of the aramid fiber to form a covalent bond. Since the polymer containing amino groups is grafted on the carbon nanotubes, the dispersibility of the carbon nanotubes can be effectively improved. The dispersion does not require a surfactant to obtain a dispersion with stable performance and good dispersibility. The process is simple, green, and conducive to industrialization. The process of forming the carbon nanotube aqueous dispersion can be adding the amino carbon nanotubes to water and using a cell crusher for ultrasonic treatment (for example, the treatment power: 600W to 1600W, the treatment time: 5min to 120min, the mass ratio of water to the amino carbon nanotubes is 100:0.05 to 1) to obtain the dispersion. The reaction conditions of the S3 step are mild and have little effect on the fiber and polymer structure. The amino content on the surface of the modified aramid fiber is 8%-40%, which is the basis for improving the mechanical properties of the composite material.

[0037] It can be seen from the above-mentioned preparation method process that the preparation method of the present invention is suitable for continuous production. Figure 2 .like Figure 2As shown, first, the aramid fiber to be treated is unwound to make the aramid fiber move forward, and an oxygen plasma treatment device is set on the movement path of the aramid fiber. As the aramid fiber moves forward through the oxygen plasma device, its surface is provided with carboxyl groups. Then, after passing through the guide roller, the aramid fiber treated with oxygen plasma passes through the dispersion of amino carbon nanotubes, and the aramid fiber continues to move forward through the heating device. The amino carbon nanotubes on the surface of the aramid fiber covalently bond with the carboxyl groups on the surface of the aramid fiber to graft the carbon nanotubes to the surface of the aramid fiber. Depending on the specific situation, the amino carbon nanotube dispersion and the heating device can be repeated. Of course, the number of repetitions can be appropriately selected according to the specific situation. These two steps can also be omitted. Finally, the modified aramid fiber is rolled up to complete the continuous production process. The continuous production method is simple, efficient, and green, and is conducive to industrial scale-up.

[0038] The modified aramid fiber surface of the present invention has abundant amino groups that can covalently bond with epoxy resin, thereby enhancing the bonding strength between the aramid fiber and the resin. In addition, the carbon nanotubes increase the surface roughness of the aramid fiber, thereby causing mechanical locking between the aramid fiber and the epoxy resin. The introduced interface layer modulus is between that of the resin and the aramid fiber, which can reduce defects at the interface of the fiber composite material under working conditions. The use of the modified aramid fiber can significantly improve the interface performance and comprehensive mechanical properties of the aramid fiber composite material. Therefore, the composite material using the modified aramid fiber resin of the present invention has stronger interface bonding force and therefore better mechanical properties.

[0039] The present invention is further described below by specific examples. However, these examples are merely exemplary and do not constitute any limitation to the scope of the present invention. In the following examples and comparative examples, the reagents, materials and instruments used are all commercially available unless otherwise specified.

[0040] Example 1

[0041] The aramid fiber was treated with oxygen plasma. The oxygen plasma atmosphere used oxygen. The aramid fiber was passed through an oxygen plasma nozzle at 500W at a speed of 1m / min. The SEM images of the aramid fiber before and after the oxygen plasma treatment were as follows: Figure 3 and 4 As shown. Figure 3 and Figure 4 It can be seen that the surface roughness of the aramid fiber increases after treatment. The functional group content is characterized by X-ray photoelectron spectroscopy (XPS), and the surface roughness is characterized by atomic force microscopy (AFM). The surface functional group content and surface roughness data of the aramid fiber before and after treatment are shown in Table 1.

[0042] Use 50% HNO 3The CNTs were pretreated with a solution and then ultrasonicated for 3 h using a cell crusher to make the average length of the CNTs reach 1 μm. 3 The CNT was treated with a solution for 12 hours to obtain a large number of carboxyl groups on its surface. An excess of polyethyleneimine with a weight average molecular weight of 10,000 was mixed with carbon nanotubes in methanol and ultrasonically dispersed for 30 minutes using an ultrasonic cell disruption system to graft polyethyleneimine onto the CNT surface to prepare PNH 2 -CNT.

[0043] PNH 2 -CNT was added to water and ultrasonicated for 20 minutes using a cell crusher to make it uniformly dispersed. The dispersion was poured into a water tank, and the oxygen plasma-treated aramid fiber was passed through the dispersion and heated at 200°C for 10 minutes to make PNH 2 -The amino groups on the CNT surface react with the carboxyl groups on the aramid fiber surface, and the two are covalently bonded. By controlling the fiber soaking time in the dispersion and the dispersion concentration, the mass fraction of carbon nanotubes on the modified fiber surface is controlled to be 1wt%, and the surface modified aramid fiber is prepared. Figure 5 The electron microscope photo of the prepared modified aramid fiber is shown. It can be seen from the photo that the roughness of the fiber surface is further increased. The surface functional group content and surface roughness data of the modified aramid fiber are shown in Table 1.

[0044] Table 1

[0045]

[0046] From the data in Table 1, it can be seen that after the aramid fiber is treated with oxygen plasma, more carboxyl groups are generated on the surface of the aramid fiber. The amino carbon nanotubes are grafted to the surface of the aramid fiber treated with oxygen plasma through the carboxyl groups on the aramid surface, thereby preparing modified aramid fiber. The carboxyl content on the surface of the modified aramid fiber is reduced, and the amino content is increased. At the same time, due to the surface grafting of carbon nanotubes, the roughness of the fiber surface is also improved. From the changes in the test data of the carboxyl content, amino content and roughness at different stages of the fiber surface, it can be seen that the method of the present invention can connect the amino-containing polymer to the surface of the aramid fiber by bonding with the carboxyl groups on the fiber surface. Therefore, the modified aramid fiber prepared by the method of the present invention has a large number of amino groups and a high roughness, so its binding force with the epoxy resin is significantly improved.

[0047] The prepared modified aramid fiber was used to prepare a modified aramid fiber / epoxy resin composite material. The preparation of aramid fiber multifilament and the tensile strength test of the dipped yarn were carried out according to the standard "GJB 348A-2018". The sample preparation process is as follows:

[0048] (1) Fiber drying treatment: Place the fiber in an electric hot air drying oven and dry it at a temperature of 70±2℃ for not less than 8h.

[0049] (2) Prepare glue solution: add 27g of p-p-diaminodiphenylmethane to every 100g of E-51 epoxy resin, use acetone as solvent, and stir evenly.

[0050] (3) Glue impregnation: Pour the prepared glue into the glue tank. The dried fiber is introduced into the glue tank through the yarn guide, tension controller, and guide wheel, and then wound on the sample winding frame through the glue scraping roller.

[0051] (4) Ensure that the tension remains constant and leave the sample for 20 hours to allow the solvent to evaporate.

[0052] (5) Curing: Place the sample winding frame wound with the impregnated multifilament into an electric heated air drying oven. The curing procedure is: 90℃ / 2h+150℃ / 3h.

[0053] The fiber-wound reinforced composite annular specimen and NOL interlaminar shear strength test are carried out according to the standard "GB / T 1458-2023". The sample preparation process is as follows:

[0054] (1) Fiber drying treatment: Place the heterocyclic aramid fiber in an oven at 105-120°C and dry it for at least 2 hours.

[0055] (2) Preparation of adhesive solution: Add 27 g of molten p-p-diaminodiphenylmethane to every 100 g of E-51 epoxy resin and stir evenly for later use.

[0056] (3) Mold preparation: Apply release agent to the cleaned mold.

[0057] (4) Glue dipping: The fiber is drawn out from the yarn ball and introduced into the glue groove through the guide roller. After the fiber is pulled out from the glue groove, the excess glue is removed with a scraper.

[0058] (5) Yarn arrangement: Wind the impregnated fibers evenly on the mold (winding speed is not more than 28 m / min).

[0059] (6) Curing: After the annular sample is wound, place it in an electric heated air drying oven. The curing procedure is: 90℃ / 2h+150℃ / 3h.

[0060] After curing, the final fiber-wound reinforced composite annular specimen was obtained.

[0061] The interfacial shear strength was tested by droplet debonding, and the sample preparation process was as follows:

[0062] (1) Fiber drying treatment: Place the fiber in an electric hot air drying oven and dry it at a temperature of 70±2℃ for not less than 8h.

[0063] (2) Prepare the glue solution: Add 1 g of polyetheramine curing agent to every 3 g of E-51 epoxy resin and stir evenly.

[0064] (3) Loading droplets on the fiber surface: The diameter of the droplets on the fiber is controlled to be 130-150 μm.

[0065] (4) Curing: The fibers and droplets are left to stand at room temperature to completely cure.

[0066] (5) Test: Load the sample and the fixture, place the blade of the fixture at the lower end of the droplet, and make the blade shear the resin on the fiber surface at 0.1mm / min, while recording the force-displacement curve. When the droplet is completely separated from the resin, the test ends. Calculate according to the following formula:

[0067]

[0068] Where τ—composite material interface shear strength (MPa)

[0069] F—resin droplet debonding load (N)

[0070] d—fiber diameter (mm)

[0071] l—Resin droplet embedding length (mm)

[0072] Sample preparation and test methods for fiber nanoindentation Young's modulus, resin nanoindentation Young's modulus, and interface layer nanoindentation Young's modulus:

[0073] The cross section of the aramid fiber multifilament is sliced ​​by ultra-thin section method. Nanoindentation test is performed on the fiber, interface and resin of the fiber multifilament cross section to test and record the nanoindentation Young's modulus.

[0074] For comparison, untreated aramid fiber was used to prepare aramid fiber / epoxy resin composites in the same way. The mechanical properties of the aramid fiber / epoxy resin composites before and after surface modification are shown in Table 2.

[0075] Table 2

[0076]

[0077] It can be seen from the data in Table 2 that the mechanical properties of the composite material formed by the modified aramid fiber of the present invention are greatly improved compared with the composite material formed by the untreated aramid fiber. The introduced interface layer modulus is between that of the resin and the aramid fiber, which can reduce the defects at the interface of the fiber composite material under working conditions.

[0078] Figure 6 , Figure 7 and Figure 8The electron microscope photos of the untreated aramid fiber, the aramid fiber treated with oxygen plasma, and the modified aramid fiber prepared in Example 1 after being pulled out of the resin are shown in FIG. By comparing the three pictures, it can be seen that the pulled-out part of the untreated aramid fiber is the smoothest, the pulled-out part of the aramid fiber treated with oxygen plasma has some resin, and the binding force between the modified aramid fiber prepared by the present invention and the resin is further enhanced, and the micro-droplet debonding test can pull out the micro-fiber structure. It can also be seen from the above three pictures that the modified aramid fiber prepared by the method of the present invention has the strongest binding force with the resin.

[0079] Example 2

[0080] By controlling HNO 3 The treatment time controlled the average length of CNT to be 2 μm, and the other steps were the same as those in Example 1 to prepare modified aramid fiber and interface-modified aramid fiber / epoxy resin composite materials.

[0081] Example 3

[0082] By controlling HNO 3 The treatment time controlled the average length of CNT to be 5 μm, and the other steps were the same as in Example 1 to prepare modified aramid fiber and interface-modified aramid fiber / epoxy resin composite materials.

[0083] Example 4

[0084] By controlling the fiber wetting time in the dispersion and the dispersion concentration, the mass fraction of carbon nanotubes on the fiber surface was controlled to be 5wt%. The other steps were the same as in Example 1, and modified aramid fiber and interface modified aramid fiber / epoxy resin composite materials were prepared.

[0085] Example 5

[0086] By controlling the fiber soaking time in the dispersion and the dispersion concentration, the mass fraction of carbon nanotubes on the fiber surface was controlled to be 0.2 wt %. The other steps were the same as in Example 1, and modified aramid fiber and interface modified aramid fiber / epoxy resin composite materials were prepared.

[0087] Comparative Example 1

[0088] Except that the aramid fiber was not subjected to oxygen plasma treatment, other steps were the same as those in Example 1 to prepare modified aramid fiber and interface-modified aramid fiber / epoxy resin composite materials.

[0089] Comparative Example 2

[0090] Except that the carbon nanotubes were not grafted onto the aramid fibers treated with oxygen plasma, other steps were the same as those in Example 1 to prepare modified aramid fibers and interface-modified aramid fibers / epoxy resin composite materials.

[0091] Comparative Example 3

[0092] The atmosphere of the plasma treatment process was air, and other conditions were the same as those in Example 1, to prepare modified aramid fiber and interface-modified aramid fiber / epoxy resin composite materials.

[0093] Table 3 shows the contents of carboxyl and amino groups on the surface of the aramid fiber after plasma treatment in air atmosphere. For comparison, the contents of carboxyl and amino groups on the surface of the aramid fiber of Example 1 after plasma treatment in oxygen atmosphere are also listed in Table 3.

[0094] Table 3

[0095]

[0096] It can be seen from the data in Table 3 that, compared with air atmosphere, carboxyl groups are more easily generated after plasma treatment in oxygen atmosphere, and the surface amino content of carbon nanotube-grafted modified aramid fibers is also higher.

[0097] Comparative Example 4

[0098] Except that ethylenediamine was used instead of polyethyleneimine to be grafted on the surface of CNT, other conditions were the same as those in Example 1, and modified aramid fiber and interface-modified aramid fiber / epoxy resin composite materials were prepared.

[0099] Table 4 shows the amino content on the surface of the modified aramid fiber prepared in this comparative example and the average particle size of the carbon nanotube dispersion after amination treatment. For comparison purposes, the amino content on the surface of the modified aramid fiber prepared in Example 1 and the average particle size of the carbon nanotube dispersion after amination treatment are also listed in Table 4.

[0100] Table 4

[0101]

[0102] From the data in Table 4, it can be seen that, compared with small molecule amino-containing compounds, the amino-containing polymer of the present invention grafted onto carbon nanotubes has a higher amino content on the surface of the modified aramid fiber, so the binding force with the resin is higher. In addition, the average particle size of the particles in the dispersion of the amino-containing carbon nanotubes of the present invention is smaller, because the grafted polymer molecular chain is longer and contains a large number of amino groups to avoid agglomeration of the carbon nanotubes, so the particle size of the particles in the dispersion is smaller, the carbon nanotubes have better dispersibility in the dispersion, and a stable dispersion can be formed without adding a surfactant.

[0103] Comparative Example 5

[0104] Except that the aramid fiber was not treated with plasma and the carbon nanotubes were not grafted, other conditions were the same as those in Example 1, and an untreated aramid fiber / epoxy resin composite material was prepared.

[0105] The mechanical properties of the interface modified aramid fiber / epoxy resin composite materials prepared in Examples 2-5 and Comparative Examples 1-5 were tested using the same testing method as in Example 1. The test results are shown in Table 5.

[0106] Table 5

[0107]

[0108]

[0109] It can be seen from the data of Examples 1-3 in Comparative Table 5 that the mechanical properties of the prepared composite materials decrease as the length of the carbon nanotubes increases. This is because the longer the carbon nanotubes are, the worse their dispersibility in water, the smaller the specific surface area of ​​the fiber, and the interaction with the epoxy resin will decrease, so the mechanical properties will decrease. It can be seen from the test data of Examples 1, 4 and 5 that when the content of carbon nanotubes is in the range of 0.2 to 5%, the mechanical properties of the fiber can be improved. The surface amino content of the modified aramid fiber prepared in Examples 1-5 is significantly higher than that of the control example, which can effectively enhance the bonding strength between the aramid fiber and the resin, thereby further improving the interface performance and mechanical properties of the aramid fiber composite material.

[0110] Comparing the mechanical property data of each embodiment and comparative example in Table 5, it can be seen that pre-treatment of aramid fiber can improve the mechanical properties of fiber-resin composite materials, and the effect of pre-functionalization of aramid fiber surface by plasma treatment of aramid fiber in oxygen atmosphere is the best. The mechanical enhancement effect of aramid fiber grafted with carbon nanotubes modified with amino-containing polymers is better than that of small molecule modification.

[0111] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A modified aramid fiber, characterized in that: The invention comprises aramid fiber and carbon nanotube, wherein the aramid fiber and the carbon nanotube are connected via amide bonds, the carbon nanotube has a length of 1 to 5 μm, and a polymer containing amino groups is grafted on the surface of the carbon nanotube.

2. The modified aramid fiber according to claim 1, characterized in that Taking the total molar weight of atoms on the surface of the modified aramid fiber as 100%, the amino content on the surface of the modified aramid fiber is 8-40%.

3. The modified aramid fiber according to claim 1 or 2, characterized in that: Taking the total mass of the modified aramid fiber as 100%, the mass content of the carbon nanotubes in the modified aramid fiber is 0.2-5%.

4. A method for preparing the modified aramid fiber according to any one of claims 1 to 3, characterized in that: include: S1, treating aramid fiber with oxygen plasma to generate carboxyl groups on the surface of aramid fiber; S2, the carbon nanotubes used have a length of 1 to 5 μm and have carboxyl groups on the surface of the carbon nanotubes, and then a polymer containing amino groups is grafted onto the surface of the carbon nanotubes to form amino-modified carbon nanotubes; S3, grafting the amino-modified carbon nanotubes onto the surface of the aramid fiber.

5. The preparation method according to claim 4, characterized in that: In the step S1, the aramid fiber is plasma treated in an oxygen atmosphere at a power range of 150 to 700 W.

6. The preparation method according to claim 4, characterized in that: In the step S2, based on the total molar amount of carbon nanotube surface atoms with carboxyl groups as 100%, the carboxyl content on the surface of the carbon nanotubes is 3-30%.

7. The preparation method according to claim 4, characterized in that: In the step S2, the polymer containing amino functional groups is one or more of polyetheramine, polyallylamine, polyacrylamide, polyethyleneimine and polyamidoamine, and the weight average molecular weight of the polymer is 2000 to 20000.

8. The preparation method according to claim 4, characterized in that: In the step S3, the aramid fiber treated with oxygen plasma is passed through an amination-modified carbon nanotube aqueous dispersion and reacted at a temperature of 60° C. to 300° C. for 2 to 40 minutes, so that the amino group reacts with the carboxyl group on the surface of the aramid fiber to form a covalent bond.

9. An aramid fiber resin composite material, characterized in that: The modified aramid fiber comprises the modified aramid fiber according to any one of claims 1 to 3.

10. The aramid fiber resin composite material according to claim 9, characterized in that: The composite material also includes epoxy resin, and amino groups on the surface of the modified aramid fiber are covalently bonded to the epoxy resin.

Citation Information

Patent Citations

  • Super hydrophilic fabric with oil-water separation and copper ion adsorption functions and preparation method and application thereof

    CN111893752A

  • Preparation method of layer-by-layer self-assembled semiconductor fiber and transistor sensor

    CN113897785A

  • Method for interface modification and performance improvement of fiber reinforced composite material

    CN116789996A

  • Application of resin / fiber composite material in preparation of bulletproof material and bulletproof material

    CN116874833A

  • Carbon nanotubes using for recovery of radionuclides and separation of actinides and lanthanides

    US20090093664A1

Cited By

  • Preparation process and application of polyimide nanofiber membrane

    CN119980684A

  • Low-temperature plasma double-sided processing device for organic fibers in prepreg equipment

    CN120481118A

  • Flame-retardant noctilucent glass fiber reinforced plastic grating plate and preparation method thereof

    CN121379052A

  • Aramid interlayer toughening composite material added with carbon nanotubes and preparation method of aramid interlayer toughening composite material

    CN121552789A